Shotgun metagenomic analysis of the oral microbiome in gingivitis: a nested case-control study - Manzoor, Muhammed (Taylor & Francis, 2025)
Background
Gingivitis, i.e. inflammation of the gums, is often induced by dentalplaque. However, its exact link to the oral microbiota remains unclear.
Methods
In a case-control study involving 120 participants, comprising 60 cases and 60 controls (mean age (SD) 36.6 (7.6) years; 50% males), nested within a prospective multicentre cohort study, we examined theoral microbiome composition of gingivitis patients and their controlsusing shotgun metagenomic sequencing of saliva samples. Participants underwent clinical and radiographic oral health examinations, including bleeding on probing (BOP), at six tooth sites. BOP ≥33%was considered ‘generalized gingivitis/initial periodontitis’(GG/IP), and BOP <33% as ‘healthy and localized gingivitis’(H/LG). Functional potential was inferred using HUMANn3.
Results
GG/IP exhibited an increase in the abundance of Actinomyces, Porphyromonas, Aggregatibacter, Corynebacterium, Olsenella, and Treponema, whereas H/LG exhibited an increased abundance of Candidatus Nanosynbacter. Nineteen bacterial species and fourmicrobial functional profiles, including L-methionine, glycogen, andinosine-5’-phosphate biosynthesis, were associated with GG/IP. Constructing models with multiple markers resulted in a strong predictive value for GG/IP, with an area under the curve (ROC) of 0.907 (95% CI: 0.848-0.966).
Conclusion
We observed distinct differences in the oral microbiome between the GG/IP and H/LG groups, indicating similar yet unique microbial profiles and emphasizing their potential role in progression of periodontal diseases.